Desenvolvimento social: o projeto de Celso Furtado para a nação brasileira - Lins, Luiza Cristina de Oliveira (2013)
The purpose of this study is to support the relevance of Celso Furtado s ideas in order to verify if the development concept as understood by this author is relevant to the current debate about the promotion and support of a development project with greater social equality in the Brazilian economy. Furtado s intellectual production collaborates in the formulation of the economic underdevelopment and development dynamics in order to explain how the first was processed in less developed countries of the system, with the purpose of answer what were the reasons behind the Brazilian economic lateness and what mistakes prevented a country with a great potential reached the true development , the one that , according to Furtado , promotes improvements in the living conditions of the population as a whole. To achieve the proposed objectives in this research, Furtadian s concepts of underdevelopment and development were explored, which means that it has been assumed as premise that development contains economic growth, but goes beyond that by setting up a social development. It was briefly analyzed the dependent countries specificities which were pointed out by Furtado as obstacles to economic growth coupled with social development. In this regard, some issues were identified regarding the labor productivity and capital accumulation in the context of late industrialization and were evaluated the topics related with income concentration, the theses about the income distribution and points concerning structural reforms. The election of these issues is explained as being fundamental to the development, in Furtado s view. In the investigation sought to articulate how these factors is presented in the developed and underdeveloped countries, highlighting the differences. It was highlight how the author understood the economic development and underdevelopment and to identify the ideology which he took part, showing elements of structuralist and developmentalist policy endorsed by him. It was also reported Furtado s perception regarding strategies for overcoming underdevelopment, emphasizing the necessity of a State interaction in the society transformation and in the economic goals through a political, economic and social reorganization as a key tool for solving the impasse of underdevelopment.